2015
DOI: 10.1002/cam4.511
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide rewires mantle cell lymphoma response to bortezomib

Abstract: Although most of the mantle cell lymphoma (MCL) patients initially responded well to bortezomib (BTZ), the dose-dependent toxicities have greatly limited the application of BTZ to MCL. To investigate the efficacy and mechanism of arsenic trioxide (ATO) with BTZ in inducing apoptosis of MCL cells, two MCL cell lines, along with primary cells from MCL patients (n = 4), were used. Additionally, the NOD-SCID mice xenograft model of Jeko-1 cells was established to study the anti-MCL mechanisms in an in vivo setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Nude mice were subcutaneously inoculated in the right flank with 1.5 × 10 7 SU‐DHL‐4 cells suspended in 100 μ L 1× PBS. The two largest perpendicular axes were measured with standard calipers, and tumor volume was calculated using the following formula: (length) × (width) 2 /2 as previously reported . When tumors reached 5 mm in the length, mice were randomly separated into vehicle control (normal saline, n = 11) or SM1044 (5 mg/kg per day, n = 12) treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…Nude mice were subcutaneously inoculated in the right flank with 1.5 × 10 7 SU‐DHL‐4 cells suspended in 100 μ L 1× PBS. The two largest perpendicular axes were measured with standard calipers, and tumor volume was calculated using the following formula: (length) × (width) 2 /2 as previously reported . When tumors reached 5 mm in the length, mice were randomly separated into vehicle control (normal saline, n = 11) or SM1044 (5 mg/kg per day, n = 12) treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…In acute lymphoblastic leukemia (ALL), low-dose ATO sensitized glucocorticoid-resistant ALL cells to dexamethasone via an Akt-dependent pathway [113]. Jung et al and Zhao et al independently showed the synergistic anticancer effects of ATO with BOR in mantle cell lymphoma, which is an aggressive and highly incurable B-cell non-Hodgkin lymphoma [114,115]. Ding et al recently reported that combined treatment of ATO with cucurbitacin B, an effective component of the dichloromethane extraction from Trichosanthes kirilowii maxim, synergistically enhances apoptosis by inhibiting STAT3 phosphorylation in Burkitt's lymphoma cell lines both in vitro and in vivo [116].…”
Section: Other Leukemia and Lymphomamentioning
confidence: 99%
“…In MCL xenograft studies using SCID mice, the drug combination treatment prevents tumor development and prolongs animal survival [61]. Arsenic Trioxide (ATO), which has been shown to upregulate pro-apoptotic proteins and induce apoptosis in MCL through downregulation of the NFκB pathway, also displays synergy with BTZ [6263]. This has been demonstrated in multiple MCL cell lines (Jeko-1, SP-53, Mino, and REC-1) and primary patient samples.…”
Section: Preclinical Studies Of Bortezomib In Mantle Cell Lymphomamentioning
confidence: 99%